Анналы и другие сочинения - Тацит Корнелий (Библиотека античной литературы, 2009)
Коммент.: с. 619-689 Экземпляры: Аб (20091102) / Инвентарный номер: 95532 / Цена: 320 / Сис.шифр: 84(0)3 / Авт.знак: Т 24 / ББК: 84(0)3